Guideline for Using Alternative Feedstuffs for Livestock - Robert Myer; Travis Maddock (EDIS)
Revised! AN124, a 5-page fact sheet by Robert Myer and Travis Maddock, provides a list of considerations for producers who are currently using or plan to use alternative feedstuffs in their livestock operations. Includes references. Published by the UF Department of Animal Sciences, December 2009.